ANALISIS PENGARUH ATMOSFIR GERAI TERHADAP PENCIPTAAN EMOSI (AROUSAL (Fokus Ekonomi, 2011)
This research is to examine the relationship between store atmosphere and store emotionalstates (arousal and pleasure). Arousal refers to store induced feelings or alertness or excitement.Pleasure refers to the degree to which the consumer feels good, joyful, happy, and satisfied in thestore. and states intentions to perform certain store related shopping behavior, which is hedonikmotivation and utilitarian motivation. Store induced pleasure is very powerful determinant ofapproach behavior in the store. This research is based on Michon and Hong Yu’s research (2007)about “The Shopping Experience of Female Fashion Leaders”.Research data were taken from150 respondents by using questionairres which were spread in MANGO Paris Van Java Bandung.Two stages of data analysis were used in this research. First, analysis factor which is includingthe validity test. Second stage is linear regression analysis to the five major hypotheses, with 95%level of confidence. The results of this research shows that store atmosphere affects the arousal,and then arousal affects the pleasure. Pleasure will affects how consumer do their shoppingmotivation (hedonik shopping motivation and utilitarian shopping motivation. Finally it willaffects approach behavior.Keywords: perception, arousal, pleasure, shopping motivation, approach behavior.